Infectious Complication During Induction Chemotherapy in Children with Acute Myeloid Leukemia- A Single Center Study - Chowdhury, Indira; Jamal, Chowdhury Yakub; Soma, Shahinoor Akter; Diba, Farah; Kaes, Imrul; Mahmud, Zaved (Bangladesh Journal of Child Health, 2022)
Background: Acute Myeloid Leukemia (AML) contributes to about 20% of leukemia. Most of the AML patients suffer from infection. Objective: To evaluate the rate of infection, type and site of infection, organisms responsible for infection and to assess antibiotic sensitivity pattern and infection related mortality in AML. Material & Methods: Newly diagnosed AML patients aged between 1-18 years, admitted to receive induction chemotherapy were enrolled. They received induction of chemotherapy according to Modified MRC’ 12 in our department. Patient was on followup throughout the induction period and all the infectious complication occurred during this period were analyzed. Result: A total of 38 episodes of infection developed in 34 patients in both cycles of induction (1.12 episodes/ patient). Among the total 38 episodes of infection, fever was the commonest clinical presentation. In both chemotherapy cycles, 7(18.4%) episodes of infection were culture positive. A total of 9 organisms were isolated of which most of them was gram-negative. Fever without focus was found in 15(39.5%) episodes. Profound neutropenia was present in 15(39.47%) episodes and profound neutropenic episodes were found to be culture positive in 5(71.4%) cases. About 6(17.5%) patients died during 1st cycle of induction. Conclusion: Among children with AML, profound neutropenic cases had high susceptibility to culture positive infection. Further prospective study is needed to identify means to prevent infectious complication of AML patients receiving induction chemotherapy particularly in those with profound neutropenia. BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 134-140